Para educar a juventude: institucionalização e circulação de um projeto de Psicologia da Educação entre institutos salesianos de Itália e Brasil (1938-1959) - Rodolfo Luís Leite Batista (2021)
This historical research describes the process of institutionalization and circulation of an Educational Psychology project between the Salesian Pontifical Athenaeum, in Turin, and the Don Bosco Faculty of Philosophy, Sciences and Letters, in São João del-Rei, between 1938 and 1959. To carry on this research, documents were collected at the Salesian Center for Documentation and Research, in Barbacena, and at the Center for Documentation and Research in the History of Psychology, in São João del-Rei. Among these sources, academic papers published by the Salesianum journal, administrative documents of the mentioned institutions, documents of characters who participated in the historical process and photographs are highlighted. The archive was analyzed in accordance with the social history of knowledge and sought to show chronological information and social and theoretical aspects that would allow to characterize the constitution of a scientific proposal for Educational Psychology and the strategies undertaken for its circulation. It is understood that the institutionalization of psychology among the Salesians in Italy occurred through the creation of the Institute of Experimental Psychology and the Higher Institute of Pedagogy of the Salesian Pontifical Athenaeum. These institutes attended to pontifical exhortations to value neothomism, as well as responding to the development of scientific psychologies in Italy and the need for academic training for Salesians who would work in educational settings. The intellectuals of this knowledge group defended certain conceptions of education, pedagogy and psychology and, when outlining a scientific project applied to school issues, they disseminated them in different contexts. To this end, they undertook strategies for the circulation of knowledge based on the Salesian Pontifical Athenaeum, such as participation in academic events, teaching practices, research and specialized publications. In São João del-Rei, the foundation of the Don Bosco Faculty of Philosophy, Sciences and Letters took place amidst local repercussions of the debates between Catholic intellectuals and those defending the New School movement regarding the application of scientific knowledge to solve school problems. This context favored the creation of the Institute of Psychology and Pedagogy stemming from the Laboratory of Experimental Psychology, the Center for Pedagogical Studies and the Educational and Professional Guidance Service. As was the case in the Turinese institutes, the knowledge group present at the Don Bosco Faculty undertook a set of strategies for the circulation of psychology, among which the promotion of specialized events and university extension activities stand out. During the period under investigation, the Salesians and the people connected to them consolidated as a group of knowledge. Inserted in a network of circulation of psychology established among Catholic institutes, they founded entities that acted as contact zones between the knowledge produced internationally and the local demands for the application of psychology for the education of the youth. They also echoed debates about the professionalization of psychology and educational guidance and sought to approach youth in an integral way. This dissertation expands the academic production in the History of Psychology by studying the institutionalization and circulation of an Educational Psychology project applied to youth schooling, explaining the relationships between Italian and Brazilian Catholic intellectuals throughout the investigated period.